Our Words in a State of Emergency: Psychological-Linguistic Analysis of Utterances on the COVID-19 Situation in the Czech Republic - Kučera, Dalibor (Psychological studies, 2021)
UNLABELLED: The study focuses on psychological-linguistic analysis of utterances provided by N = 2522 respondents aged 18-89 years in the period of March-May 2020, for the research of JUPSYCOR (Psychological Impacts of the Coronavirus Epidemic in the Czech Republic). The utterances relate to the interpretation of the state of emergency, the COVID-19 epidemic, and its subjectively perceived impacts. Simultaneously, the study examines the relationship between the analysed texts and the results of the SEHW (Scales of Emotional Habitual Subjective Well-being) questionnaire, which determines the valence of experienced emotions. The aim of the study is to analyse the lexical and morphological layers of the utterances, especially which specific words resonated in the individual questions, what is their emotional load, and which linguistic features of the texts may refer to the respondents' positive/negative emotional response. One of the outputs based on the results of the quantitative analyses determines that the most distinctive words are connected to negative emotions and most frequently relate to social environment, anxiety, and inhibition. Furthermore, the study proves a positive correlation between a fear scale and a higher occurrence of future tense and use of emotionally negatively loaded words, especially in women. Numerous differences among the individual age and gender cohorts were also proved. The significance of the study lies predominantly in the combination of the linguistic and psychological levels of the analysis, in the utilization of two mutually complementary utterances, and in the presentation of new insights on how people use words when they face an unexpected and emotionally disturbing situation. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12646-021-00613-y.
Keywords: Text analysis; Emotions; Utterances; Subjective experience; COVID-19